Noise pollution from oil, gas, and petrochemical industries - Saha, Priyanka; Monir, Minhaj Uddin; Sarkar, Shaheen M.; Azrina, Abd Aziz (Elsevier, 2023)
The study of noise pollution from oil, gas, and petrochemical industries is critical for environmental noise specialists because it has a significant impact on human, physical, and mental health. This chapter addresses the concept of noise, noise parameters, the most disturbing and influential sounds from various industrial and commercial environments, the effect on human health and some preventive measures to reduce noise pollution. Noise is a type of sound produced at sound levels ranging from of 50–85 dB. The oil and gas industries are one of the major contributors to noise pollution in the modern world due to the use of a variety of production methods, machinery, and equipment. Long-term noise exposure from commercial sites can result in a variety of health problems, including hearing loss, high blood pressure, headaches, and abnormal mental states.